1987
DOI: 10.1111/j.1399-0039.1987.tb01581.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA‐A,B,C and DR antigens in a sample of the Tunisian population

Abstract: The HLA-A, B and DR phenotypes of 109 unrelated Tunisian individuals have been determined. The HLA-A and B antigen frequencies were compared with data reported for European Caucasoids and various Arab populations.Most similarities in antigen frequencies were seen between Tunisians and Kabyles from North Africa. A high frequency of HLA-A23 and HLA-BwSO was observed in Tunisians and all Arab populations. A very close similarity in HLA-DR antigen frequencies exists between Tunisians and European Caucasoids. Linka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…Taken together the current data cannot allow us to confirm the absence of predominant haplotype in the population of Casablanca. The genetic distance data confirm previous studies [6][7][8][9][10][11][12][13][14][15] and show that Moroccans are closely related to Maghrebian but far from Senegalese and Moroccan Jewish.…”
Section: Discussionsupporting
confidence: 89%
“…Taken together the current data cannot allow us to confirm the absence of predominant haplotype in the population of Casablanca. The genetic distance data confirm previous studies [6][7][8][9][10][11][12][13][14][15] and show that Moroccans are closely related to Maghrebian but far from Senegalese and Moroccan Jewish.…”
Section: Discussionsupporting
confidence: 89%
“…Several studies have been devoted to the analysis of HLA‐DRB1 and DQB1 in North African populations, namely Moroccan and Algerian Berbers and Arabs (Djoulah et al ., 1994; Arnaiz‐Villena et al ., 1995;Izaabel et al ., 1996), Egyptians (Hafez & El Chennawi, 1986; El Chenawi et al ., 1996) and Tunisians (Ayed et al ., 1987; Jenhani et al ., 1989; Hmida et al ., 1995). However, no Berber population was ever investigated in Tunisia despite the presence of many Berber communities.…”
Section: Introductionmentioning
confidence: 99%
“…A possible cumulative effect on VTE risk by the simultaneous transmission of the major genetic traits mentioned above has been supported by some studies (14,15) but not by other recent reports (16,17). Previous immunogenetic studies showed that Tunisian population was composed of a mixture of different ethnicities as a result of active movement of population (18,19). However, there are no reports to date associating the four genetic prothrombotic traits, nor their thrombosis relevance.…”
Section: Introductionmentioning
confidence: 97%